Invasive giant reed shifts riparian habitat mosaics, with stronger effects on birds than butterflies across spatial scales - Heather L. Mackey; Lars Y. Pomara; Julie E. Coffey; Eric M. Wood (Biological Invasions, 2026)
Giant reed ( Arundo donax ) has invaded biologically diverse riparian ecosystems in warm and arid regions globally, yet its impacts on wildlife are still poorly understood. Resolving the multi-taxa, scale-explicit impacts of giant reed in the broader context of the riparian vegetation mosaics that support wildlife can help target ecological restoration efforts. We quantified effects of giant reed and other dominant riparian vegetation on bird and butterfly habitat occupancies at two spatial scales along the Rio Grande in west Texas, USA. Birds and butterflies are diverse in riparian systems and can be efficiently surveyed, making them useful indicator taxa. We surveyed 167 sites three times per year in 2016 and 2017, and used occupancy models to relate occupancy to cover proportions of dominant vegetation types derived from high-resolution aerial imagery at two scales (100 m and 500 m radii) to assess local vs. broader floodplain-scale effects. Five of 16 bird species (31%) showed negative giant reed associations at both scales, while two bird species (13%) showed positive giant reed associations and nine (56%) showed no direct effect. In contrast, no butterfly species showed direct negative associations with giant reed. However, positive associations for both butterflies and many bird species were primarily linked at both spatial scales to the vegetation types most displaced by giant reed and most likely to benefit from its control. Overall, vegetation effects were mostly at the local scale for birds, and the floodplain scale for butterflies, although negative effects of giant reed on birds persisted at the floodplain scale despite its confinement mainly to near-channel habitats. While giant reed directly impacted riparian habitat occupancy only for birds, control efforts are likely to affect both taxa positively by restoring mesic woody and herbaceous vegetation.